Potentiometric Studies of Copper(II) Complexeswith 3-Chloro-2-hydroxy Propiophenone - SWAMI, M.B.; AKUSKAR, S.K. (Asian Journal of Chemistry, 2010)
In the present paper, the proton-ligand and metal-ligand stability constant of Cu(II) with 3-chloro-2-hydroxy propiophenone is reported.